Indian Manufacturing : A Slow Sector in a Rapidly Growing Economy - Mitra, Devashish; Ural, Beyza P. (World Bank, Washington, DC, 2012)
This paper investigates the determinants of productivity in Indian manufacturing industries during the period 1988-2000. Using two-digit industry level data for the Indian states, we find evidence of imperfect interindustry and interstate labor mobility as well as misallocation of resources across industries and states. Trade liberalization increases productivity in all industries across all states, and productivity is higher in the less protected industries. These effects of protection and trade liberalization are more pronounced in states that have relatively more flexible labor markets. Similar effects are also found in the case of employment, capital stock and investment. Furthermore, labor market flexibility, independent of other policies, has a positive effect on productivity. Importantly, per capita state development expenditure seems to be the strongest and the most robust predictor of productivity, employment, capital stock and investment. Industrial delicensing increases both labor productivity and employment but only in the states with flexible labor market institutions. Even after controlling for delicensing, the analysis shows that trade liberalization has a productivity-enhancing effect. Finally, trade liberalization benefits most the export-oriented industries located in states with flexible labor-market institutions.